Triennial review of the National Nanotechnology Initiative (Washington : The National Academic Press, 2013)
"The National Nanotechnology Initiative (NNI) is a multiagency, multidisciplinary federal initiative comprising a collection of research programs and other activities funded by the participating agencies and linked by the vision of 'a future in which the ability to understand and control matter at the nanoscale leads to a revolution in technology and industry that benefits society.' As first stated in the 2004 NNI strategic plan, the participating agencies intend to make progress in realizing that vision by working toward four goals. Planning, coordination, and management of the NNI are carried out by the interagency Nanoscale Science, Engineering, and Technology (NSET) Subcommittee of the National Science and Technology Council (NSTC) Committee on Technology (CoT) with support from the National Nanotechnology Coordination Office (NNCO).
Triennial Review of the National Nanotechnology Initiative is the latest National Research Council review of the NNI, an assessment called for by the 21st Century Nanotechnology Research and Development Act of 2003. The overall objective of the review is to make recommendations to the NSET Subcommittee and the NNCO that will improve the NNI's value for basic and applied research and for development of applications in nanotechnology that will provide economic, societal, and national security benefits to the United States. In its assessment, the committee found it important to understand in some detail--and to describe in its report--the NNI's structure and organization; how the NNI fits within the larger federal research enterprise, as well as how it can and should be organized for management purposes; and the initiative's various stakeholders and their roles with respect to research.
Because technology transfer, one of the four NNI goals, is dependent on management and coordination, the committee chose to address the topic of technology transfer last, following its discussion of definitions of success and metrics for assessing progress toward achieving the four goals and management and coordination. Addressing its tasks in this order would, the committee hoped, better reflect the logic of its approach to review of the NNI. Triennial Review of the National Nanotechnology Initiative also provides concluding remarks in the last chapter"--Publisher's description.
Summary -- Introduction -- Measuring progress and defining success in the context of federal research initiatives -- National Nanotechnology Initiative stakeholders -- Metrics, definitions of success, and data -- Planning, management, and coordination framework for the National Nanotechnology Initiative -- Technology transfer and commercialization -- Overarching and crosscutting themes and priorities -- Appendixes.
Includes bibliographical references.
Keywords: National Nanotechnology Initiative (U.S.) -- Evaluation; Nanotechnology -- Research -- United States; Technology transfer -- United States